The Impact of Establishment of Tax Land and Building Rights (BPHTB), Non-metallic Mineral and Rock Tax (MBLB), and Entertainment Tax on Local Government Revenue (A Study at Bapenda Purwakarta Regency for the Years 2019-2023) - Yudhistira Alghani; Koenta Koerniawan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Original Local Revenue (PAD) represents financial resources generated and administered by local governments, based on endogenous regional capacities including natural, human, and artificial resources. The economic growth of Purwakarta Regency has shown relatively stable development. However, there is a gap between positive economic growth and the realization of Original Local Revenue (PAD) which has never been achieved from 2019 to 2023 This research investigates the influence of BPHTB, MBLB Tax, and the Entertainment Tax on the Local Own-Source Revenue (PAD) in Purwakarta Regency during the 2019–2023 period. A quantitative method was utilized, employing multiple linear regression as the analytical tool. The data used are secondary data from the budget reports and PAD realization of Purwakarta Regency for the period 2019 to 2023. The sample used in this study is a saturated sample of the entire population, consisting of 60 data points obtained from monthly data over 5 years. The results indicate that simultaneously, BPHTB, MBLB, and Entertainment Tax have a significant effect on Original Local Revenue. However, partially, BPHTB and MBLB have a significant effect on PAD, while the Entertainment Tax does not show a significant effect. This study concludes that there is a need for evaluation and improvement of tax management strategies to enhance the effectiveness of PAD collection and support regional economic growth more optimally.